Targeting the TLR2 Receptor With a Novel Thymopentin-Derived Peptide Modulates Immune Responses - Wei, Xubiao; Zhang, Lulu; Zhang, Rijun; Wu, Rujuan; Petitte, James N.; Hou, Yanfei; Si, Dayong; Ahmad, Baseer; Guo, Henan; Zhang, Manyi; Cheng, Qiang; Tong, Yucui (Frontiers in Immunology, 2021)
The innate and adaptive immune systems act in concert to protect us from infectious agents and other harmful substances. As a state of temporary or permanent immune dysfunction, immunosuppression can make an organism more susceptible to infection, organ injury, and cancer due to damage to the immune system. It takes a long time to develop new immunomodulatory agents to prevent and treat immunosuppressive diseases, with slow progress. Toll-like receptor 2 (TLR2) agonists have been reported as potential immunomodulatory candidates due to their effective activation of immune responses. It has been demonstrated that thymopentin (TP5) could modulate immunity by binding to the TLR2 receptor. However, the fairly short half-life of TP5 greatly reduces its pharmacological potential for immunosuppression therapy. Although peptide cathelicidin 2 (CATH2) has a long half-life, it shows poor immunomodulatory activity and severe cytotoxicity, which seriously hampers its clinical development. Peptide hybridization is an effective approach for the design and engineering of novel functional peptides because hybrid peptides combine the advantages and benefits of various native peptides. In this study, to overcome all these challenges faced by the parental peptides, six hybrid peptides (CaTP, CbTP, CcTP, TPCa, TPCb, and TPCc) were designed by combining the full-length TP5 with different active fragments of CATH2. CbTP, the most potent TLR2 agonist among the six hybrid peptides, was effectively screened through in silico analysis and in vitro experiments. The CbTP peptide exhibited lower cytotoxicity than either CATH2 or TP5. Furthermore, the immunomodulatory effects of CbTP were confirmed in a CTX-immunosuppressed mouse model, which showed that CbTP has increased immunopotentiating activity and physiological stability compared to the parental peptides. CbTX successfully inhibited immunosuppression and weight loss, increased immune organ indices, and improved CD4+/CD8+ T lymphocyte subsets. In addition, CbTP significantly increased the production of the cytokine TNF-α and IL-6, and the immunoglobulins IgA, IgM, and IgG. The immunoenhancing effects of CbTP were attributed to its TLR2-binding activity, promoting the formation of the TLR2 cluster, the activation of the TLR2 receptor, and thus activation of the downstream MyD88-NF-кB signaling pathway.